Structural basis for cross-group recognition of an influenza virus hemagglutinin antibody that targets postfusion stabilized epitope - Tonouchi, Keisuke; Adachi, Yu; Suzuki, Tateki; Kuroda, Daisuke; Nishiyama, Ayae; Yumoto, Kohei; Takeyama, Haruko; Suzuki, Tadaki; Hashiguchi, Takao; Takahashi, Yoshimasa (PLoS pathogens, 2023)
Plasticity of influenza virus hemagglutinin (HA) conformation increases an opportunity to generate conserved non-native epitopes with unknown functionality. Here, we have performed an in-depth analysis of human monoclonal antibodies against a stem-helix region that is occluded in native prefusion yet exposed in postfusion HA. A stem-helix antibody, LAH31, provided IgG Fc-dependent cross-group protection by targeting a stem-helix kinked loop epitope, with a unique structure emerging in the postfusion state. The structural analysis and molecular modeling revealed key contact sites responsible for the epitope specificity and cross-group breadth that relies on somatically mutated light chain. LAH31 was inaccessible to the native prefusion HA expressed on cell surface; however, it bound to the HA structure present on infected cells with functional linkage to the Fc-mediated clearance. Our study uncovers a novel non-native epitope that emerges in the postfusion HA state, highlighting the utility of this epitope for a broadly protective antigen design.